ANALISIS KAPASITAS BADAN USAHA MILIK DESA (BUMDes) TIRTA MANDIRI DALAM PENGELOLAAN DESA WISATA DI DESA PONGGOK KECAMATAN POLANHARJO KABUPATEN KLATEN - Galuh Wahyu Endah Pratiwi; Puji Astuti (Journal of Politic and Government Studies, 2026)
This study aims to analyze the organizational capacity of BUMDes Tirta Mandiri in managing Ponggok Tourism Village, Polanharjo District, Klaten Regency. Organizational capacity is examined through four main dimensions based on Horton's (2003) theoretical framework: (1) infrastructure, technology, and financial resources; (2) networks and linkages; (3) program and process management; and (4) strategic leadership. The research employed a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. Informants were selected purposively, including the BUMDes Director, marketing management, field staff, the Head of Ponggok Village, the Chair of Umbul Ponggok UMKM, and local business actors. The findings indicate that BUMDes Tirta Mandiri has undergone significant institutional transformation, evolving from managing one tourism unit to a multidimensional business organization overseeing eleven business units with financial independence since 2014. Core strengths lie in the innovative Ponggok Kreatif (PONGKREA) program, optimization of digital platforms for tourism promotion, and strategic partnerships with leading universities and the private sector through Corporate Social Responsibility (CSR) schemes. The study also identified several structural barriers, including: ambiguity in legal entity status limiting access to capital, suboptimal financial reporting transparency, weak inter-unit coordination mechanisms, and tensions between BUMDes' business orientation and local community entrepreneurial independence. The study concludes that BUMDes Tirta Mandiri's success is a manifestation of the collective social capital of all village elements. To sustain and enhance the competitiveness of Ponggok Tourism Village, strengthening financial transparency, reorienting the UMKM empowerment model toward greater participation, improving cross-unit coordination, and pursuing sustainable tourism product innovation are imperative.